Experimental analysis of Mean shift method of tracking objects - Renuka Devi, SM (International Journal of Computer Sciences and Engineering, 2025)
Real time object tracking is a perplexing task in computer vision. Many algorithms exist in literature like Mean shift, background-weighted histogram (BWH) and Corrected background-weighted histogram(CBWH) for tracking the moving objects in a video sequence.This paper attempts to do the comparative analysis of the three methods in terms of performance parameters like Normalised Centroid Distance , Overlap and number of iterations using two types of features i.e., color histogram and color texture histogram. Experimental results show that the performance of CBWH gives better performance when compared with basic Mean shift and BWH.